Histórias e memórias de lideranças surdas em Pernambuco - Vasconcelos, Norma Abreu e Lima Maciel de Lemos (2018)
This thesis is based on his historical and cultural approach, wich recognizes the historicity of the human being, values the transmissin of socially acquiered knowledge, assumes that constitutions of the subject happens from relations with the environmment and also emphasizes that human language is conceived in social life, referring to the ideia that is her, by her and with her that the individual will be constituted. The theoretical dialogues with legal issues, with public policies and social movements that have permeated the education of the deaf person was constituted from his own narratives and thus to look at: his educational trajectory; challenges to their educacional background; the marks left by their linguistic singularity; and the school in the process of social interaction and development of these people and the emergence of deaf communit and deaf movements in Pernambuco. In this way, the objectives are: a) to outline the profile of constitution of the deaf person in the state of Pernambuco, through educational aspects, stories and memories narrated by leades of deaf movements; b) to know how in that state the deaf collective that has dominion and makes use of sign language has been formed and c) to identify how aspects of social movements were fomented and what is the role of education in this history. It is a qualitative research, based on Oral History referred to, Meihhy by Thompson, Meihy and Montenegro. The Oral History of Life reconizes and values people as subjects of their own history. Eleven deaf leaders were selected, all fluent in Pounds, residing in Pernambuco (state of Pernambuco). The results show that human development is not restricted only the biological factor, but encompasses the historical, the human and the social factor, and encompasses the historical, the human and the social. The cultural constitutucion of the interviewees was crossed by the other (deaf and listener), who, in the process of interaction, made them construct concepts and meanings that reaffirmed their reality over time. From the reports, the analyzes were organized in the follow axes: family environment, language, educacional trajectory and involvement in social movements. The family participed in social interactions without sharing sign language, except in cases of deaf parents, and dealt better with their menbers was deaf. Sign language was acquired in adolescence by the majorit, in the encounter with another deaf, in its educacional trajectory, that was marked by evasions, repetition, failure. However, the school in which Libras was present (common school or school of the deaf) was signified as na interaction loci, a place of coexistence between peers, impelling other meetings in other spaces, thus contributing to the formation of the deaf movements. The associations, militants and social participations were present in all the narratives. It is believed that it is important to carry out more research that uses the History of Life method, allowing a moment of “listening” to is collaborators, to deepen the knowledge about the education of the deaf in Brazil.